Sleep hygiene and recovery strategies in elite soccer players - Nedelec, M.; Halson, S.; Delecroix, B.; Abadia, A.-E.; Ahmadi, S.; Dupont, G. (Sports Medicine, 2015)
In elite soccer, players are frequently exposed to various situations and conditions that can interfere with sleep (e.g., playing night matches interspersed with 3 days; performing activities demanding high levels of concentration close to bedtime; use of products containing caffeine or alcohol in the period preceding bedtime; regular daytime napping throughout the week; variable wake-up times or bedtime), potentially leading to sleep deprivation. We outline simple, practical, and pharmaceutical-free sleep strategies that are coordinated to the constraints of elite soccer in order to promote sleep. Sleep deprivation is best alleviated by sleep extension; however, sleep hygiene strategies (i.e., consistent sleep pattern, appropriate napping, and active daytime behaviors) can be utilized to promote restorative sleep. Light has a profound impact on sleep, and sleep hygiene strategies that support the natural environmental light-dark cycle (i.e., red-light treatment prior to sleep, dawn-simulation therapy prior to waking) and prevent cycle disruption (i.e., filtering short wavelengths prior to sleep) may be beneficial to elite soccer players. Under conditions of inordinate stress, techniques such as brainwave entrainment and meditation are promising sleep-promoting strategies, but future studies are required to ascertain the applicability of these techniques to elite soccer players. Consuming high-electrolyte fluids such as milk, high-glycemic index carbohydrates, some forms of protein immediately prior to sleep, as well as tart cherry juice concentrate and tryptophan may promote rehydration, substrate stores replenishment, muscle-damage repair and/or restorative sleep. The influence of cold water immersion performed close to bedtime on subsequent sleep is still debated. Conversely, the potential detrimental effects of sleeping medication must be recognized. Sleep initiation is influenced by numerous factors, reinforcing the need for future research to identify such factors. Efficient and individualized sleep hygiene strategies may consequently be proposed.